2019
DOI: 10.1111/epi.14759
|View full text |Cite
|
Sign up to set email alerts
|

Neural activity in the periaqueductal gray and other specific subcortical structures is enhanced when a selective serotonin reuptake inhibitor selectively prevents seizure‐induced sudden death in the DBA/1 mouse model of sudden unexpected death in epilepsy

Abstract: Objective Sudden unexpected death in epilepsy (SUDEP) is a critical issue in epilepsy, and DBA/1 mice are a useful animal model of this devastating epilepsy sequela. The serotonin hypothesis for SUDEP proposes that modifying serotonergic function significantly alters susceptibility to seizure‐induced respiratory arrest (S‐IRA). Agents that enhance serotonergic function, including a selective serotonin reuptake inhibitor, fluoxetine, selectively prevent S‐IRA in DBA/1 mice. This study examined fluoxetine‐induce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
19
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(23 citation statements)
references
References 53 publications
(173 reference statements)
3
19
0
1
Order By: Relevance
“…As the activation of PAG and PPN both have a pain suppressing effect, the decreased FC between PAG and PPN may give rise to a reduced pain threshold underlying migraine occurrence in epilepsy. Neuroimaging study has shown decreased activity in PAG in animals with epileptic seizures (59). This is consistent with our previous findings that there is a continuing loss of vlPAG neurons in rats with chronic epilepsy and neurochemical lesion to PAG decreases the pain threshold in epileptic rats (26).…”
Section: Discussionsupporting
confidence: 91%
“…As the activation of PAG and PPN both have a pain suppressing effect, the decreased FC between PAG and PPN may give rise to a reduced pain threshold underlying migraine occurrence in epilepsy. Neuroimaging study has shown decreased activity in PAG in animals with epileptic seizures (59). This is consistent with our previous findings that there is a continuing loss of vlPAG neurons in rats with chronic epilepsy and neurochemical lesion to PAG decreases the pain threshold in epileptic rats (26).…”
Section: Discussionsupporting
confidence: 91%
“…52,53,55,56 Several studies have implicated brainstem cardiorespiratory centers as critical mediators of SUDEP and suggested that serotonin neurons are major contributors. 54 , [57][58][59][60] Other studies hypothesized intrinsic cardiac arrhythmia phenotypes as another SUDEP mechanism. Relevant to Dravet syndrome and SCN1A, cardiomyocytes differentiated from patient-derived induced pluripotent stem cells (iPSCs) have abnormal physiology, suggesting cardiac arrhythmias may contribute to SUDEP.…”
Section: Mortality-mechanisms Potential Targets For Treatmentmentioning
confidence: 99%
“…3,[15][16][17] Reduced periaqueductal gray-mediated cardiorespiratory compensatory mechanism. 18,19 Caffeine can prevent S-IRA through adenosine A 2A receptors 20 Lmx1b f/f/p mouse maximal electroshock (MES)-induced seizure model Increasing 5-HT or NE or both improves S-IRA and death. 21,22 Seizure severity and dysregulation of breathing after MES seizures in mice is increased during sleep and during light phase 23,24 SCN1A mutant Dravet syndrome mouse models Death can be prevented by mechanical ventilation and atropine.…”
Section: Animal Modelmentioning
confidence: 99%
“…67 An insufficiency in the periaqueductal gray-mediated cardiorespiratory compensatory mechanism which can be enhanced by fluoxetine may underlie the death of DBA/1 mice. 18,19 5-HT 2C receptor-null mutant mice are also susceptible to AGS and death. 68 Mice with a genetic deletion of 5-HT neurons in the central nervous system ( Lm1xb f/f/p ) show increased susceptibility to and mortality from chemically and electrically induced seizures.…”
Section: Respiratory Mechanismsmentioning
confidence: 99%